2010
DOI: 10.1080/15402001003622925
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Hygiene and Sleep Quality in Medical Students

Abstract: The aim of this study was to determine whether subjective sleep quality was reduced in medical students, and whether demographics and sleep hygiene behaviors were associated with sleep quality. A Web-based survey was completed by 314 medical students, containing questions about demographics, sleep habits, exercise habits, caffeine, tobacco and alcohol use, and subjective sleep quality (using the Pittsburgh Sleep Quality Index). Correlation and regression analyses tested for associations among demographics, sle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
100
5
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 22 publications
(34 reference statements)
25
100
5
7
Order By: Relevance
“…No statistically significant association was noted between caffeine consumption and other sleep quality parameters. Our findings are in general agreement with some previous studies [27, 28]. For instance Brick et al [27], in their study among 341 US medical students, found no significant association between caffeine use and poor sleep quality.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…No statistically significant association was noted between caffeine consumption and other sleep quality parameters. Our findings are in general agreement with some previous studies [27, 28]. For instance Brick et al [27], in their study among 341 US medical students, found no significant association between caffeine use and poor sleep quality.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in general agreement with some previous studies [27, 28]. For instance Brick et al [27], in their study among 341 US medical students, found no significant association between caffeine use and poor sleep quality. Similarly, Lund et al [28] in a large survey of a Midwestern university found caffeine consumption to be a nonsignificant predictor of sleep quality.…”
Section: Discussionsupporting
confidence: 94%
“…A vida acadêmica em faculdades e universidades é marcada por períodos de mudança, no qual a maioria dos jovens deve aprender a lidar com coerções sociais e inúmeras situações de estresse longe dos pais. A maioria das mudanças no estilo de vida dos estudantes inclui dieta não balanceada, uso de álcool, uso de tabaco, comportamentos sexuais inseguros e redução da carga horária de sono, o que pode levar a um detrimento do bem-estar dos estudantes 24,25 . 15 .…”
Section: Discussionunclassified
“…Epidemiological studies that have used convenience samples to examine associations between caffeine and sleep duration or sleep quality have found conflicting results [47,53,54,55,56]. On the other hand, investigations using randomized, population-based samples have shown shorter sleep duration is associated with higher caffeine consumption [32,57,58].…”
Section: Discussionmentioning
confidence: 99%